Time resolved growth of (N)-polycyclic aromatic hydrocarbons in engine deposits uncovered with OrbiSIMS depth profiling. Issue 17 (29th July 2022) - Edney, Max K.; He, Wenshi; Smith, Emily F.; Wilmot, Edward; Reid, Jacqueline; Barker, Jim; Griffiths, Rian L.; Alexander, Morgan R.; Snape, Colin E.; Scurr, David J.
Abstract : Insoluble carbonaceous deposits were grown in internal combustion engine components and interrogated by OrbiSIMS depth profiling, and we uncovered the composition and proposed time resolved growth mechanisms of these materials. Abstract : Carbonaceous deposits are ubiquitous, being formed on surfaces in engines, fuel systems and on catalysts operating at high temperatures for hydrocarbon transformations. In internal combustion engines, their formation negatively affects worldwide vehicle emissions and fuel economy, leading to premature deaths and environmental damage. Deposit composition and formation pathways are poorly understood due to their insolubility and the intrinsic complexity of their layered carbonaceous matrix. Here, we apply the in situ high mass resolving power capabilities of 3D Orbitrap secondary ion mass spectrometry (3D OrbiSIMS) argon cluster depth profiling on 16 lab grown deposits and evidence common molecular distributions in deposit depth and in positions relative to the combustion chamber. We observe the products of the growth of both planar and curved polycyclic aromatic hydrocarbons to form small fullerenes over time in the engine and propose possible formation pathways which explain the molecular distributions observed. These include alkyl scission, cyclisation of aliphatic side chains and hydrogen abstraction C2 H2 addition to form larger aromatic structures. We apply this pathway to previously unidentified nitrogen containing structures in deposits including quinolines and carbazoles. For the first time, 3D OrbiSIMS results were compared and validated with data from atmospheric pressure matrix assisted laser desorption ionization MS. The comprehensive characterization provided will help the development of a new generation of chemical additives to reduce deposits, and thus improve vehicle emissions and global air quality.